Optic nerve head morphology in primary open‐angle glaucoma and nonarteritic anterior ischaemic optic neuropathy measured with spectral domain optical coherence tomography. Issue 8 (21st September 2018) - Resch, Hemma; Mitsch, Christoph; Pereira, Ivania; Schwarzhans, Florian; Wasserman, Lorenz; Hommer, Anton; Reitner, Andreas; Vass, Clemens
Abstract: Purpose: Optic nerve head (ONH) parameters as well as circumpapillary retinal nerve fibre layer (RNFL) thickness values measured with two different spectral domain optical coherence tomography (SD‐OCT) machines (Spectralis ® and Cirrus ® OCT) have been compared between two patient groups, primary open‐angle glaucoma (POAG), nonarteritic anterior ischaemic optic neuropathy (NAION) and healthy controls. A comparison of the performance of the two OCT machines was made. Methods: Twenty healthy controls, 20 POAG and 20 NAION patients with comparable visual field defects were included. Comparison between groups was made using anova and post hoc t ‐tests. To evaluate the diagnostic power of OCT to differentiate POAG from NAION, a stepwise linear regression analysis of the rim‐RNFL correlation with adjusting covariates (optic disc area and age) was performed. Based on the regression formula, the area under the receiver operator characteristic (AUROC) was calculated. Results: Both glaucoma and NAION patients showed significantly smaller global RNFL thickness values compared to healthy subjects in t ‐tests (p < 0.001), while only patients with glaucoma showed significantly smaller global ONH parameters for both devices compared to healthy subjects (p < 0.001). Correlation between global ONH parameters was highly statistically significant ( r = 0.93), whereas in t ‐test a statistically significant difference between the two machines was detected (p < 0.001). Area under the receiver operator characteristic revealed a similarly good discrimination between glaucoma and NAION for Spectralis ® (0.980) and Cirrus ® OCT (0.945). Conclusion: NAION patients have similar RNFL thickness values as do glaucomatous eyes, whereas ONH parameters in NAION eyes were similar to those seen in healthy controls. This difference might help discriminating between these two different disease conditions in a chronic disease stadium, and in this regard, none of the two OCT machines performed better.